College accounting. Chapters 1-28 (Homewood, IL. Richard D. Irwin, Inc., 1993)
"College Accounting is intended for use at the undergraduate level. The text and its supplements are designed to provide entry-level students with a complete foundation in general financial accounting. The course is intended to serve as a springboard for those students entering the financial accounting field at the book keeper level, as well as for those students entering the financial accounting field at the book keeper level, as well as for those going on to a more advanced course of studies. Accounting is a skill. It uses the art of interpreting data and the science of recording those data within a disciplined system. To help the student learn the system a building block approach is used: each topic is identified, discussed, and then demonstrated."
Includes bibliographical references and index.
English text.
Keywords: Accounting